Phosphorus mediated imidazolinium to oxazolium ring rearrangement. Issue 45 (3rd November 2021) - Bawari, Deependra; Volodarsky, Solomon; Ginzburg, Yael; Jaiswal, Kuldeep; Joshi, Pooja; Dobrovetsky, Roman
Abstract : An unexpected imidazolinium ring rearrangement in the NHC-based OCO pincer-type ligand occurred upon reaction with PCl3 producing chlorophosphine with a pendant oxazolium ring. Abstract : An unexpected rearrangement occurred when an imidazolinium based OCO pincer-type ligand (1 ) reacted with PCl3 producing a chlorophosphine with a pendant oxazolium "arm" (3 ). The mechanism of this rearrangement was studied both experimentally and by density functional theory (DFT) computations. The deprotonation of 3 led to further unexpected results.